Fibre-woven earth: a systematic review of fibre optimisation for compressed earth block performance - Ning Wang; Zebiao Huang; Kaili Chen; Qi Mu; Weilu Lv (European Journal of Environmental and Civil Engineering, 2026)

Microbial mechanisms mediate divergent ecosystem responses to nitrogen and phosphorus enrichment - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Xiankai Lu; Mingkai Jiang; Donghai Wu; Qinggong Mao; Shuhao Zhou; Shanshan Qi; Zirui Mu; Yilei Zhong; Mianhai Zheng; et al. (Soil Biology and Biochemistry, 2026)

Source-oriented ecological risk assessment and prioritization of heavy metals in soils impacted by coal gangue in Southwestern China - Guixiang Luo; Siyan Lv; Nan Mu; Yongmin Wang; Jiachun Lu; Cheng Zhang; Zhenwu Tang; Dingyong Wang (Applied Soil Ecology, 2026)

Upgrading electricity and CO2 to single-cell protein in microbial electrosynthesis system via a newly isolated hydrogen-oxidizing bacterium - Zhen Fang; Siyuan Zhang; Zi-Mu Li; Wang-Tao Zhou; You Lv (Food Bioscience, 2026)

Effect of water immersion time on nanoindentation creep behavior of marl - Bo Hu; Xianqi Qin; Mengru Zeng; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Qingjun He; Chunyong Jiang; Xi Long; Jian Mu; Jianlong Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Nonlinear microbial thresholds drive non-additive soil greenhouse gas responses to compound climate extremes - Zehao Lv; Gangsheng Wang; Daifeng Xiang; Shuhao Zhou; Wanyu Li; Shanshan Qi; Yajing Han; Zirui Mu; Yilei Zhong; Shuang Li; Yuhao Pan; Jiahe Liu (Agricultural and Forest Meteorology, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Discovery of rare cycloartane-type triterpenoid sulfates from Wrightia pubescens and their neuraminidase inhibition activity - Xingxiang Chen; Jinpeng Lv; Yu Mu; Ying Jiang; Xueshi Huang; Li Han (Phytochemistry, 2026)

Impacts of continuous ultra-low temperature freezing on the evolution of pore throat characteristics and coalbed methane production in bituminous coal - Lei Qin; Siheng Lin; Niandong Chen; Feilong Zhang; Zengning Huang; Han Wang; Shiyin Lv; Miao Mu (Journal of Applied Geophysics, 2026)

The transformation of Ca/Mg-silicate to Co/Ni/Fe-silicate in biomass carbon from gourd leaves for supercapacitors - Shaoqing Zhang; Xiang Ke; Tianming Lv; Jiqi Zheng; Yang Mu; Xuchun Wang; Miao Cui; Teng Du; Changgong Meng (Chemical Engineering Journal, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Hyoscyamine Ameliorates Repetitive Behavior in NLG1 and SHANK3 Deficient-Mice - Dandan Lv; Ruining Liu; Xinyu Zhang; Siqi Peng; Wei Xie; Mingdao Mu; An Liu (Neuroscience Bulletin, 2026)

Artificial sweetener acesulfame induces oxidative stress, neurotoxicity, and glycolipid metabolic disruption in zebrafish (Danio rerio) - Xue Liu; Qian Wang; Huijuan Lv; BaoYan Mu; Yali Zhou; Xianxu Li; Min Ding; Nan Jiang; Jun Wang (Environmental Pollution, 2026)

Design of robot navigation system under spatial constraints in shiitake mushroom fruiting room - Hualu Song; Kangkang Qi; Wenjie Feng; Yuanjie Mu; Jun Li; Xiangyu Lv; Zhichao Liang; Fengyun Wang (Computers and Electronics in Agriculture, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Ultrasonic enhanced Fe-C/PDS system for sludge dewatering and carbon source release: synergy of oxidation and cracking processes - Wenye Li; Binghan Xie; Zhipeng Li; Guoyu Zhang; Zhiying Lv; Qinghao Li; Shuyu Zhao; Mu Tong; Yuanyuan Gao; Langming Bai (Bioresource Technology, 2026)

Corrigendum to “Real-time cooperative multi-target tracking with low-cost radar in complex marine environments” [Ocean Eng. 345 (2026) 123694] - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Real-time cooperative multi-target tracking with low-cost radar in complex marine environments - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Investigation of pore-fracture evolution in pre-acidified coal under NMP treatment by CT scanning - Wenbo Lv; Zhixin Jin; Cunbao Deng; Yansheng Wang; Yongliang Mu (Fuel, 2026)

A multifunctional ion-conductive hydrogel with supramolecular interactions for wearable sensing: Human motion monitoring and Morse code communication - Ying Chen; Shenghua Lv; Leipeng Liu; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She (Chemical Engineering Journal, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Numerical simulation on creep behavior of argillaceous siltstone under compression-shear coupling and humidity variations - Jiajun Ran; Bo Hu; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jian Mu; Wenbin Guo (Ocean Engineering, 2025)

Demand-driven grafting engineering of IMC/PAM ionic conductive hydrogel: Multifunctional platforms for wearable sensors and TENGs - Ying Chen; Shenghua Lv; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

Correction: Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

The landscape of decidual immune cells at the maternal–fetal interface in parturition and preterm birth - Mu Lv; Yuanhui Jia; Jiaqi Dong; Shengyu Wu; Hao Ying (Inflammation Research, 2025)

Enhancing granular sludge stability: Insights from the superior performance of biofilms - Xin Wang; Xiaoran Feng; Zhibang Mu; Mingshan Wang; Chengjian Yang; Guohui Lv; Zhihua Li (Journal of Water Process Engineering, 2025)

Construction of MXene/gelatin foam hydrogel with multi-stage porous for efficient solar-driven interfacial evaporation and ion removal - Jialong She; Shenghua Lv; Tingxiang He; Ying Chen; Yanlu Mu; Jinru Liu; Jing Xu; Xiangyi Liu; Leipeng Liu (Chemical Engineering Journal, 2025)

Hourly photosynthetically active radiation prediction in solar greenhouses using Bayesian optimized machine learning and deep learning based on limited local weather data - Menglong Wu; Ruoyu Li; Chang Lv; Aihong Dong; Fei Mu; Wenquan Niu (Computers and Electronics in Agriculture, 2025)

Hidden concerns amidst prosperity: A systematic review of international and Chinese community garden participation mechanisms from a comparative perspective - Ning Wang; Han Liang; Qi Mu; Weilu Lv (Urban Forestry & Urban Greening, 2025)

Spatio-temporal distribution characteristics and sources of organic carbon in a typical mariculture Bay: A case study of Sansha Bay, China - Xiaolong Lv; Lingyi Lei; Feipeng Wang; Rongmao Li; Cong Li; Hua Lin; Zhi Zhang; Jingli Mu (Marine Environmental Research, 2025)

Hydrogen-rich reduction coupled with wet leaching for the conversion of spent SCR catalysts into carbide solid solutions - Rong Mu; Zepeng Lv; Shaolong Li; Jilin He; Jianxun Song (Journal of Environmental Chemical Engineering, 2025)

Flexible and wearable strain sensor based on SSt/PAA/G composite hydrogel for human–machine interaction applications - Jinru Liu; Shenghua Lv; Yanlu Mu; Dequan Wei; Ying Chen; Tingxiang He; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

Cellulose-sponge hierarchical architecture-based ultra-high linearity flexible pressure sensor for magnitude and acting point detection - Shaowen Mu; Jianhong Hao; Yuqing Xia; Chenyang Hong; Jingxi Wang; Xincheng Tang; Ziqiang Wang; Xiaowen Zhu; Cancan Lv; Yunong Zhao; Siliang Wang; Xiaohui Guo (Chemical Engineering Journal, 2025)

Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

Damage and acoustic characteristics of water-saturated coals with different ranks under liquid nitrogen freezing and thawing treatments - Lei Qin; Jiawei Li; Haifei Lin; Shugang Li; Miao Mu; Shiyin Lv; Niandong Chen (Geomechanics for Energy and the Environment, 2025)

Structural evolution during processing of raw and refined coal tar pitch to mesophase pitch for needle coke - Yinda Wang; Wenqing Lv; Chunfeng Mu; Yuxin Wen; Dakui Zhang; Haifeng Liu; He Yang; Lijun Jin; Ying He; Haoquan Hu (Fuel, 2025)

Hofmeister effect guided dual-crosslinked sodium alginate-based hydrogel with super-stretchable, self-adhesive, and antibacterial properties for flexible sensors in human activity monitoring - Tingxiang He; Shenghua Lv; Ying Chen; Yanlu Mu; Jinru Liu; Jialong She; Dequan Wei; Leipeng Liu (Chemical Engineering Journal, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

In vivo imaging tool: High-brightness NIR-II “J-aggregates” based on TICT suppression strategy - Taihe Han; Shuai Mu; Qin Huang; Jiaxing Sun; Xin Lv; Yanxia Zhang; Xiaoyan Liu; Wei Guo; Haixia Zhang (Chemical Engineering Journal, 2025)

Mechanistic insights into substituent-induced hydrolytic debromination and electron flow of bromophenols under nitrate-reducing conditions - Yunhao Xu; Jing Wang; Qiang Chi; Peng Zheng; Hanjuan Lv; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Oral delivery of probiotic combined natural phenolic-metal framework with microencapsulation for prolonged intestinal retention and alleviation of inflammatory bowel disease - Mengna Zhao; Longkai Mu; Fangqin Xiang; Wenqing Lv; Haixin Jiang; Guanyu Tao; Bailiang Li (Chemical Engineering Journal, 2025)

Do emerging alternatives pose similar soil ecological risks as traditional plasticizers? A multi-faceted analysis using earthworms as a case study - Huijuan Lv; Baoyan Mu; Haixia Xu; Xianxu Li; Xiangfeng Yao; Qian Wang; Huiyan Yang; Jia Ding; Jun Wang (Journal of Hazardous Materials, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Freeze–Thaw Response of Permeability and Absorption Channel Structure and Moisture Distribution in Different Coal Ranks - Lei Qin; Sinyin Lv; Shugang Li; Hui Wang; Pengfei Liu; Miao Mu; Jiawei Li (Natural Resources Research, 2025)

Tailoring argyrodite electrolyte for enhanced interface compatibility with lithium anode - Shijie Lu; Yuxiang Zhang; Xinyu Zhang; Tianwen Yang; Haijian Lv; Zihan Li; Daobin Mu (Chemical Engineering Journal, 2025)

A β-cyclodextrin-based supramolecular photonic crystal hydrogel biosensor with macroporous structures for naked-eye visual detection of cholesterol - Xi Wang; Jingjing Mu; Junjie Ren; Hairong Yu; Xingbin Lv; Ting Liang; Changjing Cheng (Carbohydrate Polymers, 2025)

Design of a diblock-based membraneless organelle system for metabolic process control - Juntao Ke; Li Wan; Maiqi Chen; Yizheng Lv; Yuanlin Liu; Yingying Zhu; Wenli Zhang; Wanmeng Mu (Chemical Engineering Journal, 2025)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Microplastic pollution in tropical coral reef ecosystems from the coastal South China Sea and their impacts on corals in situ - Weijie Bian; Yingxu Zeng; Yurui Li; Guangshui Na; Jun Mu; Shuguo Lv; Min Liu (Journal of Hazardous Materials, 2024)

Characterization of a novel heterozygous frameshift variant in NDP gene that causes familial exudative vitreoretinopathy in female patients - Mu Yang; Li Peng; Liting Lv; Erkuan Dai; Yunqi He; Rulian Zhao; Shujin Li (Molecular Genetics and Genomics, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Association between daily circulatory emergency ambulance dispatches and short-term PM2.5 exposure in a heavily polluted area - Mingxiu Sui; Guoyuan Sui; Li Sun; Jinyue Gao; Mu Huang; Zhuo Lv; Junlong Wang; Guangcong Liu; Lianzheng Yu (Environmental Geochemistry and Health, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Decorating N-doped carbon-coated cobalt phosphide nanoparticles onto N-doped carbon nanotubes for high-performance supercapacitors and efficient methanol electro-oxidation - Xiaolin Liu; Aifeng Liu; Tian Tian; Zheng Lv; Zengcai Guo; Jingbo Mu; Xiaoliang Zhang; Yanming Wang (Fuel, 2024)

In-situ curing poly(N,N'-Methylenebisacrylamide)-based composite electrolyte reinforced with high-strength glass fiber skeleton for solid state lithium ion batteries - Yuxiang Zhang; Shijie Lu; Zhikun Zhao; Xinyu Zhang; Haijian Lv; Zhuolin Yang; Wenbin Sun; Man Xie; Daobin Mu (Chemical Engineering Journal, 2024)

A mutation in CsGME encoding GDP-mannose 3,5-epimerase results in little and wrinkled leaf in cucumber - Mengying Liu; Zhaowei Li; Yunfeng Kang; Jinzhao Lv; Zhuoshuai Jin; Siyu Mu; Hongzhong Yue; Lixia Li; Peng Chen; Yuhong Li (Theoretical and Applied Genetics, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Fosthiazate, a soil-applied nematicide, induces oxidative stress, neurotoxicity and transcriptome aberrations in earthworm (Eisenia fetida) - Can Wang; Xiangfeng Yao; Xianxu Li; Qian Wang; Nan Jiang; Xue Hu; Huijuan Lv; Baoyan Mu; Jun Wang (Journal of Hazardous Materials, 2024)

Effect of induction mode on 3D printing characteristics of whey protein isolate emulsion gel - Guohua Li; Bo Wang; Weiqiao Lv; Rongyi Mu; Yuanliang Zhong (Food Hydrocolloids, 2024)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

Optimizing flow regime for the Four Major Chinese Carps by integrating habitat suitability within reservoir operation - Zehao Lv; Gangsheng Wang; Peng Zhang; Xueshan Ai; Xin Cao; Wei Zheng; Zhenyu Mu; Bowen Yu (Journal of Hydrology, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Enhancing lead immobilization by biochar: Creation of “surface barrier” via bio-treatment - Huicong Hu; Chao-Sheng Tang; Zhengtao Shen; Xiaohua Pan; Kai Gu; Xiaoliang Fan; Chao Lv; Wen Mu; Bin Shi (Chemosphere, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

Improvement of extrudability and self-support of emulsion-filled starch gel for 3D printing: Increasing oil content - Rongyi Mu; Bo Wang; Weiqiao Lv; Jie Yu; Guohua Li (Carbohydrate Polymers, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

An Updated Genome Assembly Improves Understanding of the Transcriptional Regulation of Coloration in Midas Cichlid - Yunyun Lv; Yanping Li; Yi Liu; Zhengyong Wen; Yexin Yang; Chuanjie Qin; Qiong Shi; Xidong Mu (Frontiers in Marine Science, 2022)
Midas cichlid ( Amphilophus citrinellus ), a popular aquarium fish, attracts extensive attention from worldwide biologists mainly due to its morphological polymorphism (dark versus gold). Continuous efforts have therefore been paid to address mechanisms of its coloration variants, while it is far away from the detailed illustration of a clear regulatory network. Some limits may come from the absence of a high-quality genome assembly and a relatively accurate gene set. In this study, we sequenced about 149 Gb of nucleotide sequences of Midas cichlid, generating a genome assembly with a total size of 933.5 Mb, which exhibits a good genome continuity with a contig N50 of 10.5 Mb. A total of 25,911 protein-coding genes were annotated and about 90% completeness was achieved, which helps to build a good gene pool for understanding expressional differences of color variation. With the assistance of the final gene set, we identified a total of 277 differential expressional genes (DEGs), of which 97 up- and 180 downregulated were determined in dark-vs-gold comparisons. Two protein-protein interaction (PPI) networks were constructed from these DEGs, and three key functional modules were classified. Hub genes within each module were evaluated, and we found that the third key module contains tyrp1b , oca2 , pmela , tyr , and slc24a5 , which were previously proven to be associated with melanin formation. Two downregulated DEGs ( myl1 and pgam2 ) in the first key module may be involved in muscle movement and spermatogenesis, implying that certain side effects could result from the morphological polymorphism. The first key module, consisting of proteins encoded by upregulated DEGs that were associated with MAPK signaling, Toll-like receptor signaling, and gonadotropin-releasing hormone pathways, may contribute to a negative upstream regulation or downstream influence on melanin biosynthesis. Taken together, our new genome assembly and gene annotation of Midas cichlid provide a high-quality genetic resource for biological studies on this species, and the newly identified key networks and hub genes in dark-vs-gold comparisons enhance our understanding of the transcriptional regulatory mechanisms underlying coloration changes not only in Midas cichlid but also in other fishes from freshwater to marine ecosystems.

Identification and validation of an ECERIFERUM2- LIKE gene controlling cuticular wax biosynthesis in cabbage (Brassica oleracea L. var. capitata L.) - Jialei Ji; Wenxue Cao; Long Tong; Zhiyuan Fang; Yangyong Zhang; Mu Zhuang; Yong Wang; Limei Yang; Honghao Lv (Theoretical and Applied Genetics, 2021)

Genome-wide characterization and analysis of the anthocyanin biosynthetic genes in Brassica oleracea - Fengqing Han; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Yumei Liu; Zhansheng Li; Yong Wang; Zhiyuan Fang; Jialei Ji; Honghao Lv (Planta, 2021)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Transcriptome and plant hormone analyses provide new insight into the molecular regulatory networks underlying hybrid lethality in cabbage (Brassica oleracea) - Zhiliang Xiao; Xing Liu; Zhiyuan Fang; Limei Yang; Yangyong Zhang; Yong Wang; Mu Zhuang; Honghao Lv (Planta, 2021)

Genome-wide identification and expression analysis of the Brassica oleracea L. chitin-binding genes and response to pathogens infections - Mingzhao Zhu; Shujin Lu; Mu Zhuang; Yangyong Zhang; Honghao Lv; Jialei Ji; Xilin Hou; Zhiyuan Fang; Yong Wang; Limei Yang (Planta, 2021)
Main conclusion Chitinase family genes were involved in the response of Brassica oleracea to Fusarium wilt, powdery mildew, black spot and downy mildew. Abstract Abstract Chitinase, a category of pathogenesis-related proteins, is believed to play an important role in defending against external stress in plants. However, a comprehensive analysis of the chitin-binding gene family has not been reported to date in cabbage ( Brassica oleracea L.), especially regarding the roles that chitinases play in response to various diseases. In this study, a total of 20 chitinase genes were identified using a genome-wide search method. Phylogenetic analysis was employed to classify these genes into two groups. The genes were distributed unevenly across six chromosomes in cabbage, and all of them contained few introns (≤ 2). The results of collinear analysis showed that the cabbage genome contained 1–5 copies of each chitinase gene (excluding Bol035470 ) identified in Arabidopsis . The heatmap of the chitinase gene family showed that these genes were expressed in various tissues and organs. Two genes ( Bol023322 and Bol041024 ) were relatively highly expressed in all of the investigated tissues under normal conditions, exhibiting the expression characteristics of housekeeping genes. In addition, under four different stresses, namely, Fusarium wilt, powdery mildew, black spot and downy mildew, we detected 9, 5, 8 and 8 genes with different expression levels in different treatments, respectively. Our results may help to elucidate the roles played by chitinases in the responses of host plants to various diseases.

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

An efficient virus-induced gene silencing (VIGS) system for functional genomics in Brassicas using a cabbage leaf curl virus (CaLCuV)-based vector - Zhiliang Xiao; Miaomiao Xing; Xing Liu; Zhiyuan Fang; Limei Yang; Yangyong Zhang; Yong Wang; Mu Zhuang; Honghao Lv (Planta, 2020)

Kompetitive allele-specific PCR (KASP) genotyping and heterotic group classification of 244 inbred lines in cabbage (Brassica oleracea L. var. capitata) - Zhiyuan Li; Hailong Yu; Xing Li; Bin Zhang; Wenjing Ren; Xiaoping Liu; Zhiyuan Fang; Limei Yang; Mu Zhuang; Honghao Lv; Yangyong Zhang (Euphytica, 2020)

A time-resolved dual transcriptome analysis reveals the molecular regulating network underlying the compatible/incompatible interactions between cabbage (Brassica oleracea) and Fusarium oxysporum f. sp. conglutinans - Xing Liu; Cunbao Zhao; Limei Yang; Mu Zhuang; Yangyong Zhang; Yong Wang; Zhiyuan Fang; Honghao Lv (Plant and Soil, 2020)

Assessing flood risk in Baiyangdian Lake area in a changing climate using an integrated hydrological-hydrodynamic modelling - Y. Wang; X. Zhang; Q. Tang; M. Mu; C. Zhang; A. Lv; S. Jia (Hydrological Sciences Journal, 2019)

Comparative transcriptome analysis of cabbage (Brassica oleracea var. capitata) infected by Plasmodiophora brassicae reveals drastic defense response at secondary infection stage - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Plant and Soil, 2019)

Fine-mapping and transcriptome analysis of BoGL-3, a wax-less gene in cabbage (Brassica oleracea L. var. capitata) - Xin Dong; Jialei Ji; Limei Yang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yong Wang; Peitian Sun; Jun Tang; Dongming Liu; Yumei Liu; et al. (Molecular Genetics and Genomics, 2019)

Identification of a major QTL for seed number per silique in cabbage (Brassica oleracea L. var. capitata) using genotyping by sequencing - Xing Li; Congcong Kong; Hailong Yu; Xiaoping Liu; Zhiyuan Fang; Yumei Liu; Limei Yang; Mu Zhuang; Yong Wang; Honghao Lv; Yangyong Zhang (Euphytica, 2019)

Evaluation and selection of sources of cytoplasmic male sterility in broccoli - Jinshuai Shu; Yumei Liu; Lili Zhang; Zhansheng Li; Zhiyuan Fang; Limei Yang; Mu Zhuang; Yangyong Zhang; Honghao Lv (Euphytica, 2019)

Remote sensing monitoring of the suspended particle size in Hongze Lake based on GF-1 data - Shaohua Lei; Di Wu; Yunmei Li; Qiao Wang; Changchun Huang; Ge Liu; Zhubin Zheng; Chenggong Du; Meng Mu; Jie Xu; Heng Lv (International Journal of Remote Sensing, 2019)

Fine mapping and candidate gene identification of the genic male-sterile gene ms3 in cabbage 51S - Fengqing Han; Kaiwen Yuan; Congcong Kong; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Zhansheng Li; Yong Wang; Zhiyuan Fang; Honghao Lv (Theoretical and Applied Genetics, 2018)

Identification and characterization of resistance for Plasmodiophora brassicae race 4 in cabbage (Brassica oleracea var. capitata) - Yu Ning; Yong Wang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yumei Liu; Zhansheng Li; Limei Yang (Australasian Plant Pathology, 2018)

QTL-seq for rapid identification of candidate genes for flowering time in broccoli × cabbage - Jinshuai Shu; Yumei Liu; Lili Zhang; Zhansheng Li; Zhiyuan Fang; Limei Yang; Mu Zhuang; Yangyong Zhang; Honghao Lv (Theoretical and Applied Genetics, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Recessive male sterility in cabbage (Brassica oleracea var. capitata) caused by loss of function of BoCYP704B1 due to the insertion of a LTR-retrotransposon - Jia-lei Ji; Li-mei Yang; Zhi-yuan Fang; Mu Zhuang; Yang-yong Zhang; Hong-hao Lv; Yu-mei Liu; Zhan-sheng Li (Theoretical and Applied Genetics, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Breeding of cabbage (Brassica oleracea L. var. capitata) with fusarium wilt resistance based on microspore culture and marker-assisted selection - Hong-hao Lv; Qing-biao Wang; Li-mei Yang; Zhi-yuan Fang; Yu-mei Liu; Mu Zhuang; Yang-yong Zhang; Yu-hong Yang; Bing-yan Xie; Xiao-wu Wang (Euphytica, 2014)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Cytokine Profile of a Self-Healing Fonsecaea pedrosoi Infection in Murine Model - Hong Wang; Weidong Mu; Qing Ja; Miao Zhang; Ruie Chen; Guixia Lv; Yongnian Shen; Weida Liu (Cell Biochemistry and Biophysics, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Synthesis of novel isoquinolinone and 1,2-dihydroisoquinoline scaffolds via Ugi reaction and ring opening reaction of furans - Fei Ji; Wen-bin Yi; Mu Sun; Mei-fang Lv; Chun Cai (Molecular Diversity, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Antimicrobial activity of isolate HL-12 against Clavibacter michiganensis subsp. michiganensis in the presence of cadmium - Hai-ping Yuan; Hang Min; Zhen-mei Lv; Zi-mu Li (Ecotoxicology, 2009)